Diversity and integration in private international law - Abou-Nigm, Verónica Ruiz; Noodt Taquela, María Blanca (Edinburgh University Press, 2019)
Bringing together academics and private international lawyers from a wide range of jurisdictions and institutions, this volume explores how private international law can best contribute to the development of the global legal architecture needed to integrate our emerging multicultural world society.